2016
DOI: 10.3390/nu8040189
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Five Bioelectrical Impedance Analysis Prediction Equations against Dual X-ray Absorptiometry in Estimating Appendicular Skeletal Muscle Mass in an Adult Australian Population

Abstract: Appendicular skeletal muscle mass (ASM) is a diagnostic criterion for sarcopenia. Bioelectrical impedance analysis (BIA) offers a bedside approach to measure ASM but the performance of BIA prediction equations (PE) varies with ethnicities and body composition. We aim to validate the performance of five PEs in estimating ASM against estimation by dual-energy X-ray absorptiometry (DXA). We recruited 195 healthy adult Australians and ASM was measured using single-frequency BIA. Bland-Altman analysis was used to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…A recent Australian study found that the Sergi et al equation was the most accurate (of 5 tested) for estimating ASMM using DEXA as the reference standard (in a group of Caucasian adults, 18-83 years of age). 25 In addition, they found that the Sergi equation had better predictive ability in overweight and obese individuals (similar to the patient group in this study). In addition, a source of potential error particularly relevant for the HD population is hydration status.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A recent Australian study found that the Sergi et al equation was the most accurate (of 5 tested) for estimating ASMM using DEXA as the reference standard (in a group of Caucasian adults, 18-83 years of age). 25 In addition, they found that the Sergi equation had better predictive ability in overweight and obese individuals (similar to the patient group in this study). In addition, a source of potential error particularly relevant for the HD population is hydration status.…”
Section: Discussionsupporting
confidence: 81%
“…5 Sergi et al 24 recently developed a BIA equation for ASMM using DEXA in a Caucasian older (60+ years) population group. Yu et al 25 recently compared this equation to 4 others for ASMM in a group of healthy Australian Caucasian participants (n = 195, age range = 18-83 years, mostly from European decent).…”
Section: Introductionmentioning
confidence: 99%
“…However, estimating muscle mass can be a troublesome task, one that usually requires the use of high‐cost, time‐consuming, or health facility–restricted methods such as computed tomography and dual‐energy X‐ray absorptiometry (DEXA) . Alternatively, over the last years, ASM prediction equations based on bioelectrical impedance analysis (BIA) have been proposed . However, BIA also has limitations of its own, particularly in older subjects and clinical settings …”
Section: Introductionmentioning
confidence: 99%
“…A second strength relates to the use of bioelectrical impedance analysis to evaluate body composition. A previous report that compared bioelectrical impedance analysis with dual X‐ray absorptiometry showed that the ability to estimate the amount of skeletal muscle mass was the same with both methods . Furthermore, bioelectrical impedance analysis is a simple and non‐invasive method compared with dual X‐ray absorptiometry, including computed tomography or magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%